2019
DOI: 10.1007/s11096-019-00879-3
|View full text |Cite
|
Sign up to set email alerts
|

Medication in older patients reviewed multiple ways (MORE) study

Abstract: Background Polypharmacy in older patients can lead to potentially inappropriate prescribing. The risk of the latter calls for effective medication review to ensure proper medication usage and safety. Objective Provide insight on the similarities and differences of medication review done in multiple ways that may lead to future possibilities to optimize medication review. Setting This study was conducted in Zuyderland Medical Centre, the second largest teaching hospital in the Netherlands. Method This descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Yokukansan (TJ‐54), which consists of seven dried herbs, including licorice, is reportedly effective for dementia, insomnia, and schizophrenia ( Figure 1D ) 3,4 . Moreover, polypharmacy, an unresolved issue in the aging population, is associated with drug side effects, including fatal arrhythmia due to QT interval prolongation 5 . We herein report a cautionary case of licorice‐induced pseudoaldosteronism that precipitated the onset of TCM and subsequent fatal arrhythmia in an octogenarian patient on polypharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Yokukansan (TJ‐54), which consists of seven dried herbs, including licorice, is reportedly effective for dementia, insomnia, and schizophrenia ( Figure 1D ) 3,4 . Moreover, polypharmacy, an unresolved issue in the aging population, is associated with drug side effects, including fatal arrhythmia due to QT interval prolongation 5 . We herein report a cautionary case of licorice‐induced pseudoaldosteronism that precipitated the onset of TCM and subsequent fatal arrhythmia in an octogenarian patient on polypharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the internal validity should be comparatively high because we systematically analyzed the medications of all patients presenting to the ED over the course of 2 years, thereby minimizing selection bias. Even though we did not formally evaluate interrater reliability, we are convinced that the application of our new DP categorization markedly reduced subjective bias and terminated the blending of clinically desired and undesired DPs, which was a substantial limitation of previous studies in the field [30][31][32][33][34]36]. Our DP categorization was specifically devised by physicians for physicians with direct patient contact.…”
Section: Discussionmentioning
confidence: 96%
“…Zwietering et al investigated the prevalence of “double medications” in a cohort of 200 patients in a geriatric outpatient clinic in The Netherlands [ 30 ]. The prevalence of double medications was low, ranging from 0 to 1.9%, depending on the mode of the medication review [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, this can also serve as an explanation for the relatively low proportion of PIM prescriptions in relation to total prescriptions in our study. Although medication reviews have been demonstrated to be clinically useful, there are no uniform recommendations about which aspects of pharmacotherapy should be discussed during medication reviews (Anderson et al 2014 ; Zwietering et al 2019 ). Limitations of our study are the monocentric design and the limited number of enrolled patients.…”
Section: Discussionmentioning
confidence: 99%